A review of photovoltaic thermal (PV/T) heat utilisation with low temperature desiccant cooling and dehumidification. (January 2017) - Guo, Jinyi; Lin, Simao; Bilbao, Jose I.; White, Stephen D.; Sproul, Alistair B.
Abstract: One of the major obstacles to improving solar thermal cooling technologies is the high operating temperature requirements of most solar thermal cooling systems. This paper reviews recent advances that could reduce the required heat source temperatures for solar desiccant cooling to the range of 50°C–60°C. These approaches include (i) isothermal dehumidification (e.g. two-stage dehumidification or internal cooled dehumidification) and (ii) pre-cooling of the entry air with ambient heat sinks (e.g. indirect evaporative cooling or geothermal exchange). These techniques can potentially leads to a more thermodynamically efficient solution for utilising recovered heat from flat plate photovoltaic thermal (PV/T) collectors for desiccant regeneration. Analysis of the literature shows that obtainable outlet fluid temperatures from existing PV/T systems nearly match the low temperature desiccant cooling and dehumidification applications. Design and operation factors for achieving sufficiently high outlet fluid temperature in flat plate PV/T collectors include (i) maintaining low mass flow rate per collector area, (ii) addition of a glazed cover and (iii) hydraulic channel diameter optimisation. These factors are reviewed and case studies of complete solar PV/T desiccant cooling are examined.